A Problem-Solving Flipped Classroom Module: Developing Problem-solving Skills among Culinary Arts Students - Techanamurthy, Umawathy; Alias, Norlidah; Dewitt, Dorothy (Journal of Technical Education and Training, 2020)
Problem-solving skills are important at the workplace in Culinary Arts for initiating innovative and creative solutions. However, graduates from community colleges in Malaysia seem to have only average level of problem-solving skills, while instructors do not seem to emphasise developing problem-solving skills when conducting lessons. Hence, providing more opportunities in solving real-world problems for work is required. A Flipped Classroom approach begins with activities conducted with video lectures on key concepts and gatekeeper quizzes to be completed before class and in-class phase spent on applying concepts learned before class using problem-solving activities. In this study, a Problem-Solving Flipped Classroom (PSFC) module designed for students in the Culinary Arts programme in a Malaysian Community College based on Merrill’s First Principles of Instruction and the Cognitive Apprenticeship framework was employed and implemented among 30 first-semester students and one participating instructor in a selected Community College. The single group pretest and post test quasi-experimental design was used to investigate the effectiveness of the PSFC module for learning and problem solving. Using t-test analysis, the findings indicated that the students had significant learning gains and improvement in problem-solving skills after using the module. Hence, the PSFC module could be used in Culinary Arts at other Community Colleges and TVET institutions to improve problem-solving skills among Culinary Arts students. This is to ensure a significant amount of instruction at Community Colleges include problem-solving instruction using authentic tasks at a level suitable for students to acquire problem-solving skills required in the workforce.